Cardiac disease in pregnancy and the first year postpartum: a story of mental health, identity and connection - Jane Hutchens; Jane Frawley; Elizabeth A. Sullivan (BMC, 2022)
Abstract Background Women with cardiac disease in pregnancy and the first year postpartum often face uncertainty about their condition and the trajectory of their recovery. Cardiac disease is a leading cause of serious maternal morbidity and mortality, and the prevalence is increasing. Affected women are at risk of worsening cardiac disease, chronic illness, mental illness and trauma. This compounded risk may lead to significant and long-term negative outcomes. The aim of this study is to correct the lack of visibility and information on the experiences of women with cardiac disease in pregnancy and the first year postpartum. Methods A qualitative study using in-depth semi-structured interviews with twenty-five women who had acquired, congenital or genetic cardiac disease during pregnancy or the first year postpartum. Data were analysed and interpreted using a thematic analysis framework. Results Analysis of the interviews produced three major themes: 1) Ground zero: index events and their emotional and psychological impact, 2) Self-perception, identity and worthiness, and 3) On the road alone; isolation and connection. There was a narrative consistency across the interviews despite the women being diverse in age, cardiac diagnosis and cardiac health status, parity and timing of diagnosis. The thread prevailing over the temporal and clinical differences was one of distress, biographical disruption, identity, isolation, a necessitated re-imagining of their lives, and the process of multi-layered healing. Conclusion Acknowledging and understanding the breadth, complexity and depth of women's experiences is fundamental to improving outcomes. Our findings provide unique insights into women's experiences and challenges across a spectrum of diseases. Most women did not report an isolated trauma or distressing event, rather there was a layering and persistence of psychological distress necessitating enhanced assessment, management and continuity of care beyond the routine 6-week postpartum check. Further research is required to understand long-term outcomes and to refine the findings for specific disease cohorts to be able to respond effectively.